Detrital layer thickness in 12 varved sediment cores in Lake Mondsee and related flood events AD1976-2005 - Lucas Kämpf; Achim Brauer; Tina Swierczynski; Markus Czymzik; Philip Mueller; Peter Dulski (PANGAEA, 2015)
A succession of 23 sub-millimetre to maximum 12-mm-thick, mostly flood-triggered detrital layers, deposited between 1976 and 2005, was analysed in 12 varved surface sediment cores from meso-scale peri-alpine Lake Mondsee applying microfacies and high-resolution micro X-ray fluorescence analyses. Detailed intrabasin comparison of these layers enabled identification of (i) different source areas of detrital sediments, (ii) flood-triggered sediment flux and local erosion events, and (iii) seasonal differences of suspended flood sediment distribution within the lake basin. Additional calibration of the detrital layer record with river discharge and precipitation data reveals different empirical thresholds for flood layer deposition for different parts of the basin. At proximal locations detrital layer deposition requires floods exceeding a daily discharge of 40 m**3/s, whereas at a location 2 km more distal an hourly discharge of 80 m**3/s and at least 2 days of discharge above 40 m**3/s are necessary. Furthermore, we observe a better correlation between layer thickness and flood amplitude in the depocentre than in distal and proximal areas of the basin. Although our results are partly site-specific, the applied dual calibration approach is suitable to precisely decipher flood layer formation processes and, thereby, improve the interpretation of long flood time series from lake sediments.
Supplement to: Kämpf, L et al. (2014): Processes of flood-triggered detrital layer deposition in the varved Lake Mondsee sediment record revealed by a dual calibration approach. Journal of Quaternary Science, 29(5), 475-486, https://doi.org/10.1002/jqs.2721